197k views
22 votes
Y-20 = 0.75(x-4) solve for y

User Twenkid
by
5.9k points

2 Answers

11 votes

Transforming the expression.

y - 20 = 0.75(x - 4) |add 20 to both sides

y = 0.75(x - 4) + 20

we can simplified equation:

use the distributive property: a(b + c) = ab + ac

y = 0.75x - 0.75 ยท 4 + 20

y = 0.75x - 3 + 20

y = 0.75x + 17

User Tglas
by
6.3k points
14 votes

Answer:

y = 0.75x + 17

Explanation:

y - 20 = 0.75(x-4)

y - 20 = 0.75(x) + 0.75(-4)

y - 20 = 0.75x -3

y = 0.75x -3 + 20

y = 0.75x + 17

User Katbyte
by
6.5k points